Effects of Refractive Index Solutions on the Color of Different Luting Cements - Ceylan, G.; Ömür Dede, D.Ö.; Kulunk, Ş.; Ongoz Dede, F.Ö. (Informa Healthcare, 2013)
Purpose. The purpose of this study is to determine the effects of refractive index solutions on the color of different luting cements at different periods. Materials and methods. Fourteen disc-shaped specimens were prepared for three different universal shade luting cements. All specimens were divided into two groups and a phthalate ester and glycerol refractive index solution was applied to the specimens at different periods. Color differences (ΔE*) were calculated for before and after 5, 15, 60 min and 24 h periods of applying refractive index solutions. Data were analyzed with multiple analysis of variance (ANOVA) and mean values were compared by the Tukey HSD test (α = 0.05). Results. Periods and periods-cement interaction were statistically significant (p ≤ 0.05). There was no statistically significant difference between the mean ΔE values of refractive index solutions and cement groups (p > 0.05). Conclusion. Refractive index solutions affected the color of luting cements. © 2013 Informa Healthcare.
Keywords: Color Change; Luting Cement; Refractive Index; Refractive Index Solution